Where does the time go? Temporal patterns of pumping behaviors in mothers of very preterm infants vary by sociodemographic and clinical factors - Patel, Aloka L.; Tan, Amelia; Bucek, Amelia; Janes, Judy; McGee, Katie; Mulcahy, Delaney; Meier, Paula; Johnson, Tricia J. (Frontiers in Nutrition, 2024)
Mothers of very preterm (<32 weeks gestational age [GA]) infants are breast pump dependent and have shorter duration of milk provision than mothers of term infants. The opportunity (i.e., time) cost of pumping and transporting mother's own milk (MOM) from home to the NICU may be a barrier. There is a paucity of data regarding how much time mothers actually spend pumping.To investigate the variation in pumping behavior by postpartum week, maternal characteristics, and infant GA.Prospectively collected pump log data from mothers enrolled in ReDiMOM (Reducing Disparity in Mother's Own Milk) randomized, controlled trial included pumping date and start time and end time of each pumping session for the first 10 weeks postpartum or until the infant was discharged from the NICU, whichever occurred first. Outcomes included number of daily pumping sessions, number of minutes spent pumping per day, and pumping behaviors during 24hour periods, aggregated to the postpartum week. Medians (interquartile ranges) were used to describe outcomes overall, and by maternal characteristics and infant GA.Data included 13,994 pump sessions from 75 mothers. Maternal characteristics included 55% Black, 35% Hispanic, and 11% White and 44% <30 years old. The majority (56%) of infants were born at GA 28-31 weeks. Mothers pumped an average of less than 4 times per day, peaking in postpartum week 2. After accounting for mothers who stopped pumping, there was a gradual decrease in daily pumping minutes between postpartum weeks 2 (89 minutes) and 10 (46 minutes). Black mothers pumped fewer times daily than non-Black mothers after the first 2 weeks postpartum.On average mothers pumped less intensively than the minimum recommendation of 8 times and 100 minutes per day. However, these pumping behaviors represent significant maternal opportunity costs that should be valued by the institution and society at large.